Konsep Produksi Menurut Perspektif Etika Bisnis Islam - Silvi Indah Nurvita Sari; Anugrahi Putri Ziyadatin Ilmi; Ananta Delyana Mafikah; Hikmatus Sa'diyah; Rika Nur Amelia; Eny Latifah (Journal Economic Excellence Ibnu Sina, 2025)
This research article explores the application of Islamic business ethics in production practices in Indonesia, a country with a majority Muslim population. Utilizing qualitative research methods, and data collection methods used include journals, books and articles discussing Islamic economic business ethics. After the data sources have been collected, the author will analyze them and then make conclusions about the research. The main goal of this research is to identify how these ethical guidelines influence production processes, increase social responsibility, and encourage sustainable practices. These findings reveal that adherence to Islamic business ethics not only fosters financial success but also makes a positive contribution to the welfare and desirability of environmental society. Key principles such as honesty, justice and social responsibility are understood as important components that encourage producers to create halal and high-quality products. Furthermore, the research underlines the relevance of this ethical framework in addressing contemporary challenges in the global market, thereby reinforcing the importance of ethical considerations in production activities in Indonesia.